Czy kara ograniczenia wolności w prawie karnym skarbowym jest nadal potrzebna? - Czichy, Krzysztof (Kwartalnik Prawa Publicznego, 2015)
The purpose of the penal law amendment made in 2015 was to change the punishing policy and increase non-detention penalties share in courts verdicts. Author of the publishing tries to answer the question, how often restriction of personal liberty penalty is applied in fiscal penal cases, and first of all, should that type of penalty still be in the set of penalties in fiscal penal code.